Two additional males with X‐linked, syndromic mental retardation carry de novo mutations in HNRNPH2. Issue 2 (24th June 2019) - Jepsen, Wayne M.; Ramsey, Keri; Szelinger, Szabolcs; Llaci, Lorida; Balak, Chris; Belnap, Newell; Bilagody, Cherae; De Both, Matthew; Gupta, Raj; Naymik, Marcus; Pandey, Richa; Piras, Ignazio S.; et al.
Abstract :